AAV‐mediated delivery of an anti‐BACE1 VHH alleviates pathology in an Alzheimer's disease model. Issue 4 (30th March 2022) - Marino, Marika; Zhou, Lujia; Rincon, Melvin Y; Callaerts‐Vegh, Zsuzsanna; Verhaert, Jens; Wahis, Jérôme; Creemers, Eline; Yshii, Lidia; Wierda, Keimpe; Saito, Takashi; Marneffe, Catherine; Voytyuk, Iryna; et al.
Abstract: Single domain antibodies (VHHs) are potentially disruptive therapeutics, with important biological value for treatment of several diseases, including neurological disorders. However, VHHs have not been widely used in the central nervous system (CNS), largely because of their restricted blood–brain barrier (BBB) penetration. Here, we propose a gene transfer strategy based on BBB‐crossing adeno‐associated virus (AAV)‐based vectors to deliver VHH directly into the CNS. As a proof‐of‐concept, we explored the potential of AAV‐delivered VHH to inhibit BACE1, a well‐characterized target in Alzheimer's disease. First, we generated a panel of VHHs targeting BACE1, one of which, VHH‐B9, shows high selectivity for BACE1 and efficacy in lowering BACE1 activity in vitro . We further demonstrate that a single systemic dose of AAV‐VHH‐B9 produces positive long‐term (12 months plus) effects on amyloid load, neuroinflammation, synaptic function, and cognitive performance, in the App NL‐G‐F Alzheimer's mouse model. These results constitute a novel therapeutic approach for neurodegenerative diseases, which is applicable to a range of CNS disease targets. Synopsis: VHH and blood‐brain‐barrier (BBB)‐crossing AAV‐based vectors are combined to achieve highly‐specific, long‐term BACE1 inhibition in a mouse model of Alzheimer's disease (AD). A gene transfer strategy based on BBB‐crossing AAV vectors is developed to deliver VHH single domain antibodies directly into the CNS. VHH‐B9 is generated to target BACE1, an enzyme critical to Aβ generation in AD, and incorporated into an AAV‐PHP.B‐based vector. A single dose of AAV‐VHH resulted in long‐term VHH expression in the App NL‐G‐F mouse model, with concomitant improvements in cognitive status, amyloidosis, neuroinflammation, and synaptic function. Abstract : VHH and blood‐brain‐barrier (BBB)‐crossing AAV‐based vectors are combined to achieve highly‐specific, long‐term BACE1 inhibition in a mouse model of Alzheimer's disease (AD).